2019
DOI: 10.1515/nanoph-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

Cost-efficient nanoscopy reveals nanoscale architecture of liver cells and platelets

Abstract: Single-molecule localization microscopy (SMLM) provides a powerful toolkit to specifically resolve intracellular structures on the nanometer scale, even approaching resolution classically reserved for electron microscopy (EM). Although instruments for SMLM are technically simple to implement, researchers tend to stick to commercial microscopes for SMLM implementations. Here we report the construction and use of a “custom-built” multi-color channel SMLM system to study liver sinusoidal endothelial cells (LSECs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Work by Karolina Szafranska (Arctic University of Tromsø)supported the detrimental effect of unbalanced BCAAs on LSEC morphology, showing reduced fenestration porosity and increased scavenging capacity. This group also presented on the ability of sildenafil and its analogues to increase porosity (confirming previous data (7,8) ), without any alteration in endocytic capacity. Building on previous work demonstrating the toxic effects of palmitic acid (a FFA) on hepatic toxicity, (9) Yana Geng (University of Groningen, Groningen, the Netherlands) presented data on the toxicity of oleate and palmitate on in vitro rat LSECs.…”
Section: Lsecssupporting
confidence: 85%
See 2 more Smart Citations
“…Work by Karolina Szafranska (Arctic University of Tromsø)supported the detrimental effect of unbalanced BCAAs on LSEC morphology, showing reduced fenestration porosity and increased scavenging capacity. This group also presented on the ability of sildenafil and its analogues to increase porosity (confirming previous data (7,8) ), without any alteration in endocytic capacity. Building on previous work demonstrating the toxic effects of palmitic acid (a FFA) on hepatic toxicity, (9) Yana Geng (University of Groningen, Groningen, the Netherlands) presented data on the toxicity of oleate and palmitate on in vitro rat LSECs.…”
Section: Lsecssupporting
confidence: 85%
“…(73) However, impressive data derived from direct stochastic optical reconstruction, structured illumination, atomic force, and stimulated emission depletion microscopy presented by Peter McCourt (Arctic University of Tromsø) demonstrated that it is possible to stain and visualize the LSECs as they move between defenestrated, fenestrated, and ultrafenestrated states. (8,74) These techniques allow for the effects of therapeutic agents on the ultrastructure of LSECs to be viewed in real time. (8,67) With age, there is an accelerated development of fibrosis in the liver.…”
Section: Liver Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sildenafil also increased cGMP levels, NO synthesis and levels of phosphorylated nitric oxide synthase (pNOS). Mao et al (2019) also challenged LSEC (from young mice) and found that the actin rings (which delineate fenestrations) and actin stress fibers became more pronounced. In contrast to Hunt et al (2019) and Mao et al (2019) found that sildenafil increased fenestration diameter on average by 30%.…”
Section: Lsec and Drug Interactionsmentioning
confidence: 99%
“…NMN challenge had no apparent effects on NOS or cGMP levels in LSEC. Analysis of NMN challenged LSEC using direct stochastical optical reconstruction microscopy (dSTORM) revealed that the F-actin within LSEC was more condensed and that the actin rings delineating fenestrations became more pronounced ( Mao et al, 2019 ). The mode of NMN action in LSEC remains to be elucidated – NAD + associates with sirtuins which play a critical role in multiple cellular functions ( Imai and Yoshino, 2013 ) so the study of the role of sirtuins in fenestration biology is therefore warranted.…”
Section: Lsec and Drug Interactionsmentioning
confidence: 99%